Updates in Papular Urticaria Causes, Diagnosis, And Management: A Systematic Review: Life Sciences-Medicine - Olaythah Alraddadi, Mohammed; Saad M Alnawmasi, Norah; Farhan D Alshammari, Waleed; Kamel A Albalawi, Razan; Hussain A Hamdi, Asma; Ahmad Alqrid Ahmad, Aedah; Bader S Almutairi, Amjad; Suliman Aljammaz, Samaher; Abdulkarim M Alatawi, Sarah; Ibrahim H Alomari, Lubna; Faiz S Aljohani, Shahad (International Journal of Life Science and Pharma Research, 2022)
Abstract: Papular urticaria is a frequent disturbing disease characterized by chronic or recurrent papules that are a hypersensitive reaction to mosquito, bedbug, flea, and other insect bites. PubMed, Web of Science, Science Direct, EBSCO, and Cochrane library were searched. Study articles were screened by title and abstract using Rayyan QCRI then a full-text assessment was implemented. This review investigates the published literature regarding the causes, diagnosis, and management of papular urticaria. Eight studies were included, with 527 patients with papular urticaria. Most cases were diagnosed morphologically and clinically, and only one study depended on light and electron microscopy. Arthropods and hypersensitivity reactions were the most common causes. This review reported the frequency of hypersensitivity reactions to insect bites, flea bites, bedbug bites, and domestic urticaria bites. According to reports, morphological patterns were used to diagnose most cases clinically. Insect repellents, antihistamines, antipruritic, topical steroids, and symptomatic treatments were used to treat the majority of patients with papular urticaria.